RESULTS AND CHARACTERISTICS OF 5G HOLE DRILLING AND THE FIRST TAPPING OF LAKE VOSTOK - N. Vasil’ev I.; V. Lipenkov Ya.; A. Dmitriev N.; A. Podolyak V.; V. Zubkov M.; Н. Васильев И.; В. Липенков Я.; А. Дмитриев Н.; А. Подоляк В.; В. Зубков М. (Ice and Snow, 2015)
We present here a brief description of the drilling operations in the deep 5G hole at the Russian Vostok Station with more detailed account of the final stage of this long-term project successfully ended on February 5, 2012 with the first Lake Vostok unsealing. Relevant information on the borehole design and the technical characteristics of the downhole and surface drilling equipment is given. The peculiarities of the drilling process are discussed in connection with changing properties of the penetrated ice. The data analysis allows defining the main factors that influence the efficiency of the electromechanical drill system at great depths. It is shown that the elevated temperature of ice and its coarse-crystalline texture are mainly responsible for the significant for the showing-down of ice coring in the bottom sections of ice sheets observed at Vostok and at other drilling sites in Antarctica and Greenland as well. Based on the large amount of experimental data obtained in the course of the deep drilling at Vostok, we discuss the processes which occur in the borehole during the ice drilling and unsealing the sub-ice water bodies. In particular, we investigate the conditions for occurrence of hydraulic fracturing in the hole and the possible effect of the hydrofrac on the height of the water column that have risen in hole 5G after the Lake Vostok unsealing. Finally we formulate the drill equipment requirements and process specifications that would ensure the best performance of an electromechanical drill and trouble-free drilling operations at different depths in a borehole up to the bottom of ice sheet. Приводятся сведения об истории бурения глубокой скважины 5Г на российской станции Восток и обсуждаются технологические параметры вскрытия подледникового озера Восток. Описаны конструкция скважины и даны технические характеристики скважинного и поверхностного оборудования. Рассмотрены особенности бурения глубоких скважин на разных глубинах. На основе большого объёма экспериментальных данных, накопленных при ...